THE EFFECT OF WORK-LIFE BALANCE, WORK STRESS, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. WIJAYA INTI NUSANTARA SAWIT PALOPO CITY - Nurfaisyah, Nurfaisyah; M Anwar, Suhardi; Junaidi, Junaidi (Universitas Islam Lamongan, 2025)
The purpose of this study was to determine how work-life balance, work stress, and work environment affect employee performance at PT. Wijaya Inti Nusantara Sawit, Palopo City. This study used a quantitative method with a population of 140 employees. Because the population is more than 100, the sampling method used is the Slovin formula with a total of 104 employees as respondents. Multiple linear regression is a data analysis method used to test the hypothesis. The results show that (1) work-life balance affects employee performance at PT. Wijaya Inti Nusantara Sawit, Palopo City positively and significantly; (2) work stress does not affect employee performance at PT Wijaya Inti Nusantara Sawit, Palopo City, does not have a positive and insignificant effect; and (3) the work environment affects employee performance at PT Wijaya Inti Nusantara Sawit, Palopo City positively and significantly